Β‐adrenergic Receptor Blocker ICI 118, 551 Selectively Increases Intermediate‐Conductance Calcium‐Activated Potassium Channel (IKCa)‐Mediated Relaxations in Rat Main Mesenteric Artery. Issue 6 (16th January 2018) - Ozkan, Melike Hacer; Uma, Serdar
Abstract: Endothelial IKC a and/or SKC a channels play an important role in the control of vascular tone by participating in endothelium‐dependent relaxation. Whether β‐AR antagonists, mainly used in hypertension, affect endothelial KC a channel function is unknown. In this study, we examined the effect of the β2‐AR antagonist and inverse agonist ICI 118, 551 on the IKC a /SKC a channel activity by assessing functional relaxation responses to several agonists that stimulate these channels. Mesenteric arterial rings isolated from male Sprague Dawley mounted to organ baths. Acetylcholine elicited IKC a ‐ and SKC a ‐mediated relaxations that were abolished by TRAM‐34 and apamin, respectively. ICI 118, 551, which did not dilate the arteries per se, increased the IKC a ‐mediated relaxations, whereas SKC a ‐mediated relaxations remained unaltered. Same potentiating effect was also detected on the IKC a ‐mediated relaxations to carbachol and A23187, but not to NS309. Neither acetylcholine‐induced nitric oxide‐mediated relaxations nor SNP relaxations changed with ICI 118, 551. The PKA inhibitor KT‐5720, the selective β2‐AR agonist salbutamol, the selective β2‐AR antagonist butoxamine, the non‐selective β‐AR antagonist propranolol, and the inverse agonists carvedilol or nadolol failed to affect the IKC a ‐mediated relaxations. ICI 118, 551‐induced increase was not reversed by salbutamol or propranolol as well. Besides, low potassium‐induced relaxations in endothelium‐removed arteries remained the same in the presence of ICI 118, 551. These data demonstrate a previously unrecognized action of ICI 118, 551, the ability to potentiate endothelial IKC a channel‐mediated vasodilation, through a mechanism independent of β2‐AR antagonistic or inverse agonistic action. Instead, the enhancement of acetylcholine relaxation seems likely to occur by a mechanism secondary to endothelial calcium increase.